Initial Investigation of Small Colony Variants of Staphylococcus Aureus in Chronic Rhinosinusitis. Issue 1 (January 2015) - Gitomer, Sarah A.; Ramakrishnan, Vijay R.; Malcolm, Kenneth C.; Kofonow, Jennifer M.; Ir, Diana; Frank, Daniel N.
Background: Small colony variants (SCVs) are a metabolically inactive form of bacteria that can be difficult to eradicate. To examine whether SCVs contribute to Staphylococcus aureus persistence in chronic rhinosinusitis (CRS), we compared the prevalence of S. aureus SCVs in CRS patients and healthy controls. Methods: Endoscopically guided middle meatus samples were collected from 23 CRS patients and 12 controls. Samples were cultured and screened for the presence of phenotypically small colonies. Candidate SCV isolates were classified by 16S rRNA gene sequencing. To further characterize the capacity of S. aureus isolates to form SCVs when stressed, colonies underwent a gentamicin exposure assay. Results: Among CRS patient samples, 15 were culture positive for S. aureus (65.2%), and of those, two grew putative SCVs on selective media (8.7%). However, neither was genetically confirmed to be S. aureus upon sequencing. In healthy controls, eight specimens were culture positive for S. aureus (66.7%), and of these, two grew putative S. aureus SCVs on selective media (16.7%); but again, neither was confirmed to be S. aureus by 16S analysis. None of the four patients colonized with SCVs had evidence of sinonasal disease at a mean follow-up of eight months. S. aureus isolates from CRS patients and controls were equally likely to form SCVs with gentamicin exposure. Conclusion: S. aureus SCVs were not associated with CRS in the current study. Their role in refractory CRS remains theoretical, and further research is warranted to determine whether S. aureus SCVs may reside in the intracellular compartment.